Effect of adrenergic antagonism on the growth hormone, prolactin and cortisol response to a synthetic opioid agonist in man. - Bouloux, P; Grossman, A; Allolio, B; Delitala, G; Besser, G (1986)
The intravenous administration of 250 micrograms D-Ala2-MePhe4-Met-enkephalin-O-ol (DAMME) caused a marked increase in circulating growth hormone (GH) and prolactin (PRL), and a fall in cortisol, in 14 normal subjects. Neither the alpha 1-antagonist thymoxamine, nor the alpha 2-antagonist yohimbine, significantly altered the GH and PRL responses to DAMME, suggesting that in man the growth hormone- and prolactin-releasing effects of exogenous opioids are not mediated through adrenoceptor pathways. The fall in cortisol induced by DAMME was not affected by thymoxamine, but was significantly attenuated by yohimbine, indicating that opioids may lower circulating cortisol via an interaction with noradrenergic pathways.